Analysis of Arabic Language Education Textbooks of Muhammadiyah Junior High School Grade 7 in Terms of Content and Language Feasibility - Wahyuni, Sri; Daroini , Slamet (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2024)
Teaching material is one of the elements in the curriculum that occupies a very important position, where this teaching material will be a source of student knowledge while making it easier for teachers to organize and carry out learning. Therefore, the feasibility of a textbook is very important. However, in reality there are problems related to the content in the textbook. Content and language feasibility are two of the four eligibility criteria for a textbook that must be considered. This research is a quantitative research with survey method. Data collection methods are observation, and questionnaires. Data analysis begins with statistical calculation techniques, namely calculating the results of analysis scores from educational experts, linguists and practitioners. Then proceed with describing the data and discussing the results of the research and drawing conclusions. Teaching Book of Arabic Language Education SMP Muhammadiyah grade 7 in terms of content feasibility has been categorized in a very feasible category by educational experts with a percentage of 91.9% and by practitioners with a percentage of 92.9% and in terms of language feasibility has been categorized in a very feasible category by linguists with a percentage of 83.1% and by practitioners with a percentage of 90.6%. The results of this study indicate that the Arabic Language Education textbook of Muhammadiyah Junior High School grade 7 is very feasible to be used in the teaching and learning process in class. Keywords: Content Feasibility, Language Eligibility, Textbooks